Case Study: B. abortus Outbreak in Egyptian Dairy Farm with a Special Reference to Control Programs - Salah, Khaled; El-Diasty, Mohamed; El-Hofy, Fatma I.; Wareth, Gamal; Abd El Tawab, Ashraf A. (Journal of Advanced Veterinary Research, 2022)
A storm of abortions was reported in a Holstein dairy farm (150 heads) at Dakahlia governorate, Delta region, Egypt. The abortion rate was 25.9% among the pregnant cows between the 5th and 8th months of pregnancy. All animals inside the farm (n=150) have been sampled for a serological survey. Additionally, abomasal contents, retained placenta, and milk samples were sampled for bacteriological isolation and characterization of the causative pathogen of abortion. A total of 16.6 % of the aborted animals were seropositive with RBPT and BAPAT. Abortion materials and retained fetal membranes showed significant association with seropositivity. Moreover, B. abortus bv. 1 was bacteriologically isolated and then underwent confirmation by AMOS-PCR in samples of 20 animals. Increase awareness of occupational personnel on the farm, immediate slaughtering of the sero-positive animals, and vaccination of the sero-negative animals with B. abortus RB51 vaccine (2ml subcutaneous for each animal), are collectively recommended for a rapid control of brucellosis on the farm and for prevention of further abortions.